Intercourse as Discourse in Alexa Hennig von Lange’s Relax - Corinna Kahnke (Studies in 20th & 21st Century Literature, 2011)
While gender has long been an abiding concern of Popliteratur, pop writers (in particular female authors) are often criticized for simply reflecting, if not positively endorsing, negative forms of postfeminism—an attitude that negates the accomplishments of emancipation by regressing to traditional ideas of what it means to be a woman. Some critics suggest that pop texts re-inscribe the gender binary by presenting, even glorifying, long-established gender roles. In response to such a reception, this article investigates Alexa Hennig von Lange’s iconic but much criticized novel Relax (1999) in order to illustrate the reflective and critical nature of Popliteratur. I demonstrate how Hennig von Lange critically engages with images of masculinity, femininity and feminism, thereby queering (that is to say de-stabilizing), pre-conceived notions of gender and identity. Ultimately, texts such as Relax foreshadow the demands of the new popfeminists roughly a decade later.
Keywords: gender; popliterature; female authors; postfeminism; gender binary; gender roles; Alexa Hennig von Lange; Relax; masculinity; femininity; feminism; queer; queering; gender identity